2007
DOI: 10.1212/01.wnl.0000277638.63767.b8
|View full text |Cite
|
Sign up to set email alerts
|

Are Parkinson disease patients protected from some but not all cancers?

Abstract: There is substantial evidence based on well designed epidemiologic studies for low cancer rates in patients with Parkinson disease (PD). This risk reduction cannot be attributed to the recognized low life-long incidence of smoking in patients with PD, as not only smoking-related cancers but also non-smoking-related ones are less common in PD. Whereas the risk for most cancers appears to be relatively low in patients with PD, breast cancer and melanomas occur more frequently in the PD population as compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 80 publications
3
110
3
1
Order By: Relevance
“…In this way, the BH4 domain of Bcl-xL is maintained and the full-length protein can exert its anti-apoptotic function p-Bcl-xL by PINK1 protects from CCCP-induced death G Arena et al suggesting that common genes and pathways might be implicated in both diseases. 38 PINK1 was identified for the first time through a gene expression screening in ovarian carcinoma cells overexpressing PTEN, a key tumor suppressor gene, which is mutated in several malignancies. 39 Recent data have proposed a novel function of PINK1 in promoting carcinogenesis, insofar PINK1 silencing was shown to downregulate Bcl-xL expression in bladder cancer cells, sensitizing them to ROS-mediated cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the BH4 domain of Bcl-xL is maintained and the full-length protein can exert its anti-apoptotic function p-Bcl-xL by PINK1 protects from CCCP-induced death G Arena et al suggesting that common genes and pathways might be implicated in both diseases. 38 PINK1 was identified for the first time through a gene expression screening in ovarian carcinoma cells overexpressing PTEN, a key tumor suppressor gene, which is mutated in several malignancies. 39 Recent data have proposed a novel function of PINK1 in promoting carcinogenesis, insofar PINK1 silencing was shown to downregulate Bcl-xL expression in bladder cancer cells, sensitizing them to ROS-mediated cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Still, considering more recent studies, in particular cohort studies, evidence for a lower cancer risk among PD patients is fairly consistent. Underlying mechanisms are unclear, although several authors suggested shared genetic factors, pointing out that several of the genes involved in familial PD also are implicated in cancer [617][618][619].…”
Section: Cancermentioning
confidence: 99%
“…A similar association of PD with decreased risk of almost all common cancers, including those that are strongly related to smoking (lung, colorectal and bladder cancer), was reported in 2007. [102,103] There were two notable exceptions: melanoma and breast carcinoma that were actually more common in patients with PD than in age-matched controls. Similarly, in individuals with Down syndrome aged over 30 years, the risk of leukaemia (specifically, acute myeloid leukaemia, but also acute lymphoblast leukaemia (ALL)) is significantly elevated, whereas the risk of most solid tumours (including breast cancer) is actually lower than the population risk.…”
Section: Cancer and Londd: Extremes Of A Wide Spectrum?mentioning
confidence: 99%